Elementos para una filosofía de las relaciones internacionales. (2015)
This article offers an alternative to the study of the international system through the so-called “philosophy of order”. From a critical synthesis of chaos theory and general systems theory, this proposal will analyze the dynamics of change and the possibilities for performers to determine the course of their actions. These actions are limited within a certain order, confined in an order that facilitates the change, creating subsequent forms of rebalancing the system and the dissipation modes of chaos that actors create chaos to live together in an endurable order. And it is at this point that the agency capacity of the international actor is put to test.